Population-Pharmacokinetic Modeling of Tildrakizumab (MK-3222), an Anti-Interleukin-23-p19 Monoclonal Antibody, in Healthy Volunteers and Subjects with Psoriasis - Jauslin, Petra; Kulkarni, Pooja; Li, Hanbin; Vatakuti, Suresh; Hussain, Azher; Wenning, Larissa; Kerbusch, Thomas (Clinical pharmacokinetics, 2019)
Background Tildrakizumab is an anti-interleukin-23p19 monoclonal antibody recently approved for the treatment of chronic plaque psoriasis. Methods This analysis characterizes the population pharmacokinetics of subcutaneous tildrakizumab and identifies covariates influencing exposure in 2098 healthy volunteers and subjects with psoriasis. Tested covariates included body weight, formulation type, sex, age, race, serum albumin, creatinine clearance, Japanese origin, prior treatment with a biologic agent, subject status (subjects with psoriasis vs. healthy volunteers), and ethnicity. Results The pharmacokinetics was described by a one-compartment model with first-order absorption and elimination kinetics, and inter-individual variability on clearance, volume of distribution, and absorption rate constant. The pharmacokinetics was characterized by low clearance and limited volume of distribution. In subjects with psoriasis, the geometric mean clearance (coefficient of variation) was 0.32 L/day (38%), volume of distribution was 10.8 L (24%), and absorption and elimination half-life were 1.5 days (18%) and 23.4 days (23%), respectively, with an absorption lag time of 1.2 h. For the 100-mg dose, steady-state area under the plasma concentration vs. time curve for one dosing interval and maximum plasma concentration were 305 µg*day/mL (41%) and 8.1 µg/mL (34%), respectively. Steady state was achieved by 16 weeks with the clinical regimen (dosing on week 0 and week 4 and every 12 weeks thereafter) with 1.1-fold accumulation in maximum plasma concentration. Healthy subjects had 31% higher bioavailability than subjects with psoriasis. Subjects with increased body weight had a lower area under the plasma concentration-time curve at steady state vs. those with lower body weight. The modeled exposures were contained within clinical comparability bounds for all covariates including body weight. Conclusions The pharmacokinetics of tildrakizumab behaves like a typical monoclonal antibody without requiring dosage adjustment. Trial Registration NCT01729754, NCT01225731, NCT01722331.